LEGAL EDUCATION OF PHARMACISTS IN A CONTEXT OF SOCIETY DEMOCRATIZATION AND THE EUROPEAN STANDARDS OF EDUCATION IN UKRAINE - I. M. Alieksieieva (Zaporozhye State Medical University, 2015)
In order to determine the urgent need for scientific applied research to improve legal education and legal education in higher educational institutions of the pharmaceutical and medical profile conditions have been explored by such methods as observation, comparison, analysis and synthesis, identification, description and interpretation. It has been established that the main source of specific legal education must be current legislation and international instruments ratified by the Ukrainian parliament - the VerkhovnaRada, which is common tool of general civil and professional relationships regulation. This suggests that state government should strive to keep this professional category not only highly professional, but also highly moral, highly cultured and the right conscious. The aim of the article - scientific research and theoretical study of social meaning and motivation to legal education in the departments of pharmaceutical profile in terms of the university. Materialsandmethodsofresearch The research is based on an analysis of academic publications and monographs on the theory of state and law, philosophy, psychology, legal psychology and copyright research and professional publications on the current state of legal education, legal trainingand legal culture of students in Ukraine. Results and discussion The man, society, state - three interrelated nature of social and historical phenomena, the emergence and development of which are caused by objective natural laws. Each of these institutions of social life is in constant dynamics and relationships. Prominent in the specified interaction takes man with his natural rights and interests. But that does not mean it has to be a passive consumer goods, which should create the society and the state. Fundamental preconditions for the improvement of society and the state, as the basis for a comfortable, safe human existence is a constant development and improvement of himself (physical, moral, spiritual, humanitarian, professional, etc.) and active influence on social and public processes. ConclusIons: 1. Formation of Ukraine as a democratic, legal and social state regulated by the Constitution - the Basic Law and legislation on European integration, is therefore binding. Fundamental to achieve these ideals is the formation of personality with high level of legal awareness and legal culture. It can only be resolved in the process of focused, unified, systematic and evidence-based legal education, combined with a legal training. 2. The general motivation of a citizen to legal education caused by the following factors: growing as more and more political and economic international integration; rather complex economic and social relations at the national level; requirements of state vocational qualification standards; formation needs and ability to actively protect the established interests of law and the rights of both their own and other participants in public relations. 3. The major attention need legal education students. This is due to the following factors: 1) The specified category of youth is relatively independent, rather numerous social actors, carrier group sense of justice; 2) justice students largely determine the mode and the state of law and order in society; 3) students, opposed to other social groups, most masters, professions and specialties are needed in terms of transformation of society; 4) It is the main carrier of intellectual and physical potential of the nation and the only source of replenishment of highly qualified human resources of the state.4. Pharmacy legislation, Pharmacy Education, Pharmacists